Think Positive, be Positive: Expressive Writing Changes Young People’s Emotional Reactions Towards the COVID-19 Pandemic - Mariën, Sofie; Poels, Karolien; Vandebosch, Heidi (Frontiers in Education, 2022)
Combining the transactional model of stress and coping and expressive writing theory, this research studied whether writing on one’s personal experiences with the COVID-19 pandemic may improve young people’s emotional reactions to the situation. A standard expressive writing instruction was compared to a positive writing instruction (writing about the positive aspects) and a coping writing instruction (writing about previous experiences and how these are helpful to cope with the situation). The results showed that participants in the positive writing instruction experienced a significantly higher positive change in feelings in relation to the COVID-19 pandemic in comparison with participants in the other writing instructions. This relationship was not mediated by the relative contents of writing. The results can help in designing online social support interventions for coping with the COVID-19 pandemic and stressful events in general.